Gene expression signatures prognostic for relapse in stage I testicular germ cell tumours. (31st May 2018) - Lewin, Jeremy; Soltan Ghoraie, Laleh; Bedard, Philippe L.; Hamilton, Robert J.; Chung, Peter; Moore, Malcolm; Jewett, Michael A.S.; Anson‐Cartwright, Lynn; Virtanen, Carl; Winegarden, Neil; Tsao, Julie; Warde, Padraig; et al.
Abstract : Objectives: To identify differentially expressed genes between relapsed and non‐relapsed clinical stage I testicular germ cell tumours (TGCTs). Materials and Methods: We reviewed patients with clinical stage I non‐seminoma and seminoma from an institutional database (2000–2012) who were managed by active surveillance. Patients with non‐relapsed non‐seminoma and non‐relapsed seminoma were defined as being relapse‐free after 2 and 3 years of surveillance, respectively. RNA extraction and gene expression analysis was performed on archival primary tumour samples and gene‐set enrichment analysis (GSEA) was conducted in order to identify differentiating biological pathways. Results: A total of 57 patients (relapsed non‐seminoma, n = 12; relapsed seminoma, n = 15; non‐relapsed non‐seminoma, n = 15; non‐relapsed seminoma, n = 15) were identified, with a median (range) relapse time of 5.6 (2.5–18.1) and 19.3 (4.7–65.3) months in the relapsed non‐seminoma and relapsed seminoma cohorts, respectively. A total of 1 039 differentially expressed genes were identified that separated relapsed and non‐relapsed groups. In patients with relapse, GSEA revealed enrichment in pathways associated with differentiation, such as skeletal development (i.e. FGFR1, BMP4, GLI2, SPARC, COL2A1 ), tissue (i.e. BMP4, SPARC, COL13A1 ) and bone remodelling (i.e. CARTPT, GLI2, MGP ). A discriminative gene expression profile between relapsed and non‐relapsed cases was discovered when combining non‐seminoma and seminoma samples using 10‐ and 30‐probe signatures; however, this profile was not observed in the seminoma and non‐seminoma cohorts individually. Conclusion: A discriminating signature for relapsed disease was identified for clinical stage I TGCT that we were not able to identify by histology alone. Further validation is required to determine if this signature provides independent prognostic information to standard pathological risk factors.